Inflammation—The role of ATP in pre‐eclampsia. (6th September 2019) - Fodor, Paul; White, Benjamin; Khan, Raheela
Abstract: Sterile inflammation may be initiated by molecules in the host organism that signal "damage" or "danger" also known as danger‐associated molecular pattern (DAMPs). In pre‐eclampsia (PE), a variety of DAMPs may be involved in the etiology or exacerbation of the disorder. Adenosine 5'‐triphosphate (ATP) is a key intracellular energy molecule as well as a ligand for purinergic receptors. In humans, under physiological conditions, extracellular ATP (eATP) levels are distinctly low, but can rise to several hundred fold when cells become injured, stressed, or even necrotic. This often initiates a sterile inflammatory response with eATP acting as a DAMP. Extracellular ATP and its derivative nucleotides synthetized by endonucleotidases exhibit many of their effects through purinergic receptors, via inflammatory cascades and the production of proinflammatory molecules. This is clearly seen in the P2X7 gated receptor, which is linked to release of cytokines of the interleukin‐1 family. Considering its fundamental role in innate immunity, an imbalance of P2X7 receptor activation may lead to deleterious effects in the coordination of placental vessel tone via the synthesis of various proinflammatory cytokines. This review explores the implication of DAMPs, specifically ATP and uric acid in the inflammation associated with PE.